Tranexamic Acid for Prevention of Hematoma Expansion in Intracerebral Hemorrhage Patients With or Without Spot Sign. Issue 8 (18th May 2021) - Ovesen, Christian; Jakobsen, Janus Christian; Gluud, Christian; Steiner, Thorsten; Law, Zhe; Flaherty, Katie; Dineen, Rob A.; Christensen, Louisa M.; Overgaard, Karsten; Rasmussen, Rune S.; Bath, Philip M.; Sprigg, Nikola; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The computed tomography angiography or contrast-enhanced computed tomography based spot sign has been proposed as a biomarker for identifying on-going hematoma expansion in patients with acute intracerebral hemorrhage. We investigated, if spot-sign positive participants benefit more from tranexamic acid versus placebo as compared to spot-sign negative participants. Methods: TICH-2 trial (Tranexamic Acid for Hyperacute Primary Intracerebral Haemorrhage) was a randomized, placebo-controlled clinical trial recruiting acutely hospitalized participants with intracerebral hemorrhage within 8 hours after symptom onset. Local investigators randomized participants to 2 grams of intravenous tranexamic acid or matching placebo (1:1). All participants underwent computed tomography scan on admission and on day 2 (24±12 hours) after randomization. In this sub group analysis, we included all participants from the main trial population with imaging allowing adjudication of spot sign status. Results: Of the 2325 TICH-2 participants, 254 (10.9%) had imaging allowing for spot-sign adjudication. Of these participants, 64 (25.2%) were spot-sign positive. Median (interquartile range) time from symptom onset to administration of the intervention was 225.0 (169.0 to 310.0) minutes. The adjusted percent difference in absolute day-2 hematoma volume between participants allocated to tranexamic versus placebo was 3.7% (95% CI, −12.8% to 23.4%) for spot-sign positive and 1.7% (95% CI, −8.4% to 12.8%) for spot-sign negative participants ( P heterogenity =0.85). No difference was observed in significant hematoma progression (dichotomous composite outcome) between participants allocated to tranexamic versus placebo among spot-sign positive (odds ratio, 0.85 [95% CI, 0.29 to 2.46]) and negative (odds ratio, 0.77 [95% CI, 0.41 to 1.45]) participants ( P heterogenity =0.88). Conclusions: Data from the TICH-2 trial do not support that admission spot sign status modifies the treatment effect of tranexamic acid versus placebo in patients with acute intracerebral hemorrhage. The results might have been affected by low statistical power as well as treatment delay. Registration: URL: http://www.controlled-trials.com ; Unique identifier: ISRCTN93732214.